1989
DOI: 10.1002/mcs.1220010609
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid extraction of chlorpyrifos methyl from wheat at part per billion levels

Abstract: Abstract. The use of supercritical fluid extraction (SFE) to recover pesticides from environmental matrices was investigated using chlorpyrifos methyl spiked on a wheat kernel substrate. Volume-based extraction recovery profiles were generated to determine the pressure, temperature, and fluid composition that yielded the maximum analyte recovery and minimum extraction time. On-line coupled microcolumn liquid chromatography-gas chromatography (LC-GC) with electron capture detection was used to effect cleanup of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Campbell et al observed a decreased recovery of chlorpyrifosmethyl in dry wheat and resorted to the use of 2% methanol modifier to improve recovery. 15 Our results emphasize how the modifying and dispersing effect of water can serve a similar purpose as the addition of an organic solvent.…”
Section: Effect Of Drying Agent : H 2 O Ratiosupporting
confidence: 51%
See 1 more Smart Citation
“…Campbell et al observed a decreased recovery of chlorpyrifosmethyl in dry wheat and resorted to the use of 2% methanol modifier to improve recovery. 15 Our results emphasize how the modifying and dispersing effect of water can serve a similar purpose as the addition of an organic solvent.…”
Section: Effect Of Drying Agent : H 2 O Ratiosupporting
confidence: 51%
“…Supercritical fluid extraction (SFE) is a promising method of extraction for pesticide residues in fruits and vegetables. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The advantages of a lower solvent viscosity, higher rate of mass transfer, and a wide range of densities for supercritical fluids versus liquid solvents often lead to a reduced extraction time and increased selectivity in SFE. Other practical advantages of SFE versus organic-solvent-based methods of extraction include: no need for solvent evaporation, reduced solvent consumption, less hazardous waste generation, smaller space requirements, increased automation, and the use of less glassware.…”
mentioning
confidence: 99%
“…Recently, interest in the use of supercritical fluid extraction (SFE) as an analytical technique in the field of pesticide residue analysis has increased considerably. The technique has been applied to the extraction of pesticides and/or metabolites from soil (Brady et al, 1987;Engelhardt and Gross, 1988; McNally and Wheeler, 1988; Wheeler and McNally, 1989;Snyder et al, 1992;Locke, 1993;Lopez-Avila et al, 1990, 1993 and from food products (Campbell et al, 1989;France and King, 1991;Hooper and King, 1991;Thomson and Chesney, 1992;Wigfield and Lanouette, 1993). SFE yields superior extraction efficiencies and offers a number of potential advantages compared to conventional solvent extraction methods for isolating pesticide residues from biological and environmental sample matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Recoveries (93-111%) and precision (8.5% RSD) obtained with the supercritical fluid technique compared favorably to those obtained by a conventional column clean-up method. Campbell et al investigated the SFE of chlorpyrifos methyl from wheat followed by on-line LC/GC/ECD (393). Extraction recovery profiles were generated to determine the maximum analyte recovery and the minimum extraction time.…”
Section: Environmental Samplesmentioning
confidence: 99%